Sense transcription through the S region is essential for immunoglobulin class switch recombination - Haddad, Dania; Oruc, Zéliha; Puget, Nadine; Laviolette-Malirat, Nathalie; Philippe, Magali; Carrion, Claire; Le Bert, Marc; Khamlichi, Ahmed Amine (The EMBO journal, 2011)
Class switch recombination (CSR) occurs between highly repetitive sequences called switch (S) regions and is initiated by activation‐induced cytidine deaminase (AID). CSR is preceded by a bidirectional transcription of S regions but the relative importance of sense and antisense transcription for CSR in vivo is unknown. We generated three mouse lines in which we attempted a premature termination of transcriptional elongation by inserting bidirectional transcription terminators upstream of Sμ, upstream of Sγ3 or downstream of Sγ3 sequences. The data show, at least for Sγ3, that sense transcriptional elongation across S region is absolutely required for CSR whereas its antisense counterpart is largely dispensable, strongly suggesting that sense transcription is sufficient for AID targeting to both DNA strands. Class switch recombination (CSR) is preceded by sense and antisense transcription of the switch (S) regions. While sense transcription of the S region is needed for CSR, antisense transcription is not essential.